Pengaruh Security, Trust, Usability, dan Usefulness terhadap Kepuasan Pengguna pada Aplikasi SeaBank - Eti Yulianti; Nurhadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The escalating adoption of digital banking applications underscores the imperative for a comprehensive comprehension of factors influencing user satisfaction. This study seeks to scrutinize the impact of security, trust, usability, and usefulness on user satisfaction within the SeaBank digital banking application. Employing a quantitative research methodology, data were collected through a questionnaire distributed to 271 respondents utilizing the SeaBank application in Indonesia. Multiple linear regression analysis was employed for data analysis. The findings revealed that collectively, security, trust, usability, and usefulness significantly affect user satisfaction. Specifically, trust, usability, and usefulness individually exhibit a substantial positive influence on user satisfaction, while security demonstrates an insignificant positive impact. Consequently, enhancing elements of trust, ease of use, and application utility can heighten user satisfaction in the realm of digital banking applications. The practical implications of these findings can offer valuable insights to digital banking service providers, guiding efforts to enhance both quality and user satisfaction. A strategic emphasis on these identified factors is anticipated to provide a foundation for the development of more efficacious strategies aimed at optimizing the user experience within the digital banking domain.